Translanguaging as Comedy Content on Instagram: A Sociolinguistic Study - Nurfithri; Neneng Farida Rahmah (Universitas Islam Negeri Palopo, 2026)
The growing use of social media has transformed multilingual communication by enabling users to combine diverse linguistic resources in creative and dynamic ways. While translanguaging has been widely examined in educational and classroom settings, its role in digital humor remains underexplored. This study investigates translanguaging practices in Instagram comedy content from a sociolinguistic perspective, focusing on how multilingual resources are utilized to construct humor and social meaning. Employing a qualitative descriptive design, the study analyzed multilingual utterances from selected comedy videos posted on the Instagram account @rsydna.a. The data were purposively selected from 312 available posts and analyzed across four linguistic levels: morphology, semantics, syntax, and phonology. The findings reveal that the content creator integrates Sundanese, Indonesian, and English as a unified communicative repertoire rather than as separate linguistic systems. Morphological translanguaging emerged as the most dominant pattern, followed by semantic, phonological, and syntactic translanguaging. The analysis demonstrates that hybrid word formation, meaning transfer, structural adaptation, and localized pronunciation function as important resources for humor production, identity construction, and audience engagement. These findings suggest that translanguaging in digital comedy is not merely a form of language mixing but a dynamic sociolinguistic practice through which multilingual speakers creatively negotiate linguistic and cultural boundaries. By examining translanguaging across multiple linguistic levels in social media comedy content, this study extends translanguaging research beyond educational contexts and contributes to a broader understanding of multilingual communication in contemporary digital environments.